Efektivitas Pelaksanaan Bimago Dalam Meningkatkan Tingkat Kelulusan Penerimaan Santri Baru Masuk Gontor - Muthia Azizah (HAWARI : Jurnal Pendidikan Agama dan Keagamaan Islam, 2025)
The purpose of writing this article is to find out whether gontor entrance guidance (bimago) is effective in increasing the graduation rate of new students to enter gontor. Bimago is a tutoring institution that aims to prepare new students who want to continue their education at Pesantren Gontor. With this bimago, it can help new students prepare themselves for the gontor entrance graduation exam. Prospective students studying in bimago learn lessons that will be tested in the gontor entrance exam. Gontor is a modern Islamic boarding school whose center is in East Java, which has branches in various regions in Indonesia and has the same goal, namely so that children who want to continue their education in Gontor can graduate. The research method used is a qualitative method with a descriptive approach, researchers directly plunged to observe how effective bimago is in increasing the graduation rate of new students entering gontor. As for the results of this study that bimago (gontor entrance guidance) is very helpful for new students who want to continue their education at Gontor Modern Islamic Boarding School and effective in increasing the graduation rate of new students to enter gontor, students who previously participated in bimago graduated to become new students of gontor, compared to those who did not follow bimago before